(3eQBI GdLfGf hYHQI GdjbXGf aj eYQaI MhGOK GdReGf hJbdH CMhGd GdEfSGf hJGQjN HYV GdeTghQjfs - (3GdjGaYj , Yaja GdOjf YHO Gddg Hf CSYO Hf Ydj GdjGaYj Gdjefj, Yaja GdOjf,J (B768 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdeJhMO HGdEdgjI hGdceGd agPG cJGH dNUI hENJUQJg eeG PcQ Cgd GdJhGQjN hGdSjQ , hChdhG GdMaX hGdEJbGf , ai GdJYQa HhajGJ HYV GdeTghQjf GdePchQjf GdCYjGf hSejJg eQBI GdReGf s
(3BNQgG (B:s
(3hai gPG GdJGQjg Ydi GdNeSjf HYO GdSHYeGFI EfJgGDg hGdMeO ddg GdPi HMeOg NJe GdcdGe hEHJOGDg JfGgi JGQjNi GdPi EfJbjJ eYXeI ef JGQjg GdPgHi hGHf NdcGf Je GdJGQjN GdehShe HeQBI GdLfGf s
(3HgG fXGe GdJYbjHIs
(3YdjgG JedcGJ CbOegG SfI (B1078 (3g`s
(3cJHJ GdSfhGJ hHYV GdcdeGJ ajgG HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B72 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B34s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs